Cytological Study of the Morphological Variants of Tribulus terrestris Linn - Bhansali, A. K. (Indian Forester, 1980)
Cytololgicai investigation of the morphological variants of T. terrestris Linn. did not reveal any relationship between morpphological diversity and variation in chromosome number. It has been suggested that morphological characters should not be used indiscriminately in determining the ploidal nature of an organism.The most reliable criterion for determining the ploidy of a plant is the chromosome number.